Method for preparing high-entropy carbide gradient solid solution strengthening layer by double glow plasma metallurgy

CN122879659APending Publication Date: 2026-10-09TAIZHOU JICUI METAL NEW MATERIALS TECHNOLOGY CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202611105378.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-07-24
Publication Date
2026-10-09

AI Technical Summary

Technical Problem

[0004]等离子体离子轰击持续为工件提供热能,形成高温扩散环境,溅射产生的高能活性合金原子沉积在工件表面,在浓度梯度、高温条件,以及离子轰击诱发大量晶格缺陷的协同作用下向基体内部固相扩散,伴随基体元素反向互扩散,合金元素含量自表层向基体持续递减,进而形成梯度冶金层,然而,该梯度演化过程自发进行,梯度曲线的形态、各深度处的合金元素浓度难以主动调控,梯度区间的宽度和表层元素的富集程度依赖温度、保温时间等工艺参数,容易出现表层成分饱和、内部元素梯度衰减过快的问题

Benefits of technology

[0023]1.本发明中采用分阶段梯度构建工艺,依次形成高熵合金底层、过渡层与高熵碳化物表面强化层,在过渡层制备阶段同步调控源极电压、工件极偏压、含碳气体流量及源极与工件极间距多项参数,减少自发扩散对梯度层的影响,便于控制梯度区间宽度与表层元素富集程度,减少表层成分饱和、内部元素梯度衰减过快问题的出现。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN122879659A_ABST
    Figure CN122879659A_ABST
Patent Text Reader

Abstract

The application discloses a method for preparing a high-entropy carbide gradient solid solution strengthening layer by double-glow plasma metallurgy, and relates to the field of alloy surface modification.The technical scheme is as follows: the titanium alloy base material and the high-entropy alloy target material are polished, the base material is loaded on a workpiece electrode, the target material is loaded on a source electrode, an interelectrode distance adjusting mechanism is locked, inert gas is introduced after the cavity is sealed and vacuumized, the two electrode power sources are connected after the gas pressure is stabilized, the surface oxide film is removed, the voltage of the two electrodes is simultaneously raised, the high-entropy alloy bottom layer is formed by low-speed sputtering, carbon-containing gas is introduced, the voltage of the two electrodes and the gas flow are simultaneously controlled, and the interelectrode distance is gradually reduced to prepare a transition layer, the process parameters are stabilized to continuously deposit, the high-entropy carbide solid solution strengthening layer is generated, the voltage of the two electrodes is gradually reduced to zero after the gradient layer is prepared, the carbon-containing gas and the inert gas passages are cut off, and the base material is cooled to room temperature in the furnace and taken out.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of alloy surface modification, and more specifically, to a method for preparing high-entropy carbide gradient solid solution reinforced layers using dual-glow plasma metallurgy. Background Technology

[0002] Alloys are new homogeneous metallic materials with complete metallic properties, formed by fusing two or more metallic elements, or metallic and non-metallic elements, through processes such as melting and sintering. When the properties of the alloy matrix itself are insufficient to meet the requirements of complex working conditions, surface modification treatment is required to improve the surface hardness, wear resistance, and corrosion resistance of the alloy.

[0003] Existing alloy surface modification methods mainly include vapor deposition technology, high-energy beam modification, and dual-glow plasma metallurgy technology. Among them, dual-glow plasma metallurgy technology involves filling the cavity with low-pressure argon gas and applying negative bias voltage to the workpiece and the source electrode respectively. Argon ions continuously bombard the source electrode target material, sputtering the alloy elements in the target material into active atoms. The atoms are transported in the plasma space and deposited on the surface of the workpiece, realizing a gradient reinforcement layer that is metallurgically bonded to the substrate on the substrate surface.

[0004] Plasma ion bombardment continuously provides heat energy to the workpiece, creating a high-temperature diffusion environment. High-energy active alloy atoms generated by sputtering are deposited on the workpiece surface. Under the synergistic effect of concentration gradient, high temperature conditions, and a large number of lattice defects induced by ion bombardment, they diffuse into the solid phase inside the matrix. Accompanied by the reverse interdiffusion of matrix elements, the content of alloy elements continuously decreases from the surface layer to the matrix, thus forming a gradient metallurgical layer. However, this gradient evolution process is spontaneous, and the shape of the gradient curve and the concentration of alloy elements at each depth are difficult to actively control. The width of the gradient interval and the enrichment degree of surface elements depend on process parameters such as temperature and holding time, which can easily lead to problems such as surface composition saturation and excessively rapid decay of the internal element gradient.

[0005] Therefore, in order to solve the above-mentioned technical problems, this application proposes a method for preparing high-entropy carbide gradient solid solution reinforced layers using dual-glow plasma metallurgy. Summary of the Invention

[0006] To address the shortcomings of existing technologies, the present invention aims to provide a method for preparing high-entropy carbide gradient solid solution reinforced layers using dual-glow plasma metallurgy.

[0007] To achieve the above objectives, the present invention provides the following technical solution: a method for preparing a high-entropy carbide gradient solid solution reinforced layer using dual-glow plasma metallurgy, the method comprising the following steps:

[0008] S1. Material pretreatment: The titanium alloy substrate and the high-entropy alloy target are polished, and the polished titanium alloy substrate and the high-entropy alloy target are placed in a solution for ultrasonic cleaning and drying.

[0009] S2. Material installation: Place the pretreated titanium alloy substrate on the workpiece electrode of the dual-glow plasma device, place the high-entropy alloy target on the source electrode of the dual-glow device, and lock the workpiece electrode and source electrode spacing adjustment mechanism.

[0010] S3. Oxide film treatment: Seal the double glow plasma equipment, evacuate the cavity, introduce inert gas into the inner cavity of the double glow plasma equipment, stabilize the cavity gas pressure, turn on the workpiece extreme bias power supply and the source voltage power supply to remove the surface oxide film.

[0011] S4. Forming the bottom layer: Maintaining stable inert gas flow and cavity pressure, simultaneously increasing source voltage and workpiece bias voltage, performing low-rate sputtering to form a high-entropy alloy bottom layer on the surface of the titanium alloy substrate.

[0012] S5. Forming a transition layer: Open the valve of the carbon-containing gas pipeline, adjust the source electrode voltage, workpiece electrode bias voltage and carbon-containing gas flow rate synchronously at a constant rate, and gradually reduce the distance between the source electrode and the workpiece electrode through the adjustment mechanism to form a transition layer.

[0013] S6. Forming a surface layer: The source voltage, workpiece bias voltage, carbon-containing gas flow rate and electrode spacing are set stably and maintained for a stable time to form a high-entropy carbide reinforcement layer on the surface of the substrate.

[0014] S7. Cooling and Removing the Part: Reduce the source voltage and workpiece bias voltage to zero, reduce the flow rate of carbon-containing gas until the valve on the carbon-containing gas pipeline is closed, close the valve on the inert gas inlet pipeline, and remove the substrate after it has cooled to room temperature with the furnace.

[0015] Preferably, in S1, the titanium alloy substrate is polished with sandpaper of grit 240 to 1200#, and polished sequentially from coarse to fine. The titanium alloy substrate is then cleaned in an acetone solution.

[0016] Preferably, in S1, the high-entropy alloy is polished with sandpaper of grit 240-2000#, polishing from coarse to fine. The high-entropy alloy is then cleaned in anhydrous ethanol. The elements and their proportions in the high-entropy alloy target material are as follows: Ti: 8.09%, Zr: 15.42%, Hf: 30.18%, Nb: 15.71%, Ta: 30.60%.

[0017] Preferably, in S3, the inert gas is argon with a purity of ≥99.99%, the cavity pressure is stable at 30-50 Pa, the workpiece bias voltage is -300--500 V, the source voltage is 700-900 V, and the processing time is 10-30 min.

[0018] Preferably, in S4, the argon flow rate is 30-50 sccm, the source voltage is increased to 900-1100V, the workpiece bias voltage is increased to -500--700V, and the sputtering time is 30-60 min.

[0019] Preferably, in S5, the carbon-containing gas is methane, the source voltage is adjusted from 900-1100V to 1100-1300V, the workpiece bias voltage is adjusted from -500--700V to -700--900V, the carbon-containing gas flow rate is increased from 0 sccm to 10-20 sccm, the distance between the source and workpiece electrodes is gradually reduced from 15-20 mm to 10-12 mm, and the time for forming the transition layer is 30-90 min.

[0020] Preferably, in S6, the source voltage is 1100-1300V, the workpiece bias voltage is -700-900V, the carbon-containing gas flow rate is 10-20sccm, the electrode spacing is 10-12mm, and the stabilization time is 60-120min.

[0021] Preferably, in S7, the cooling rate is 5-10°C / min, and the temperature at which the substrate cools to room temperature is 20-30°C.

[0022] Compared with the prior art, the present invention has the following beneficial effects:

[0023] 1. This invention employs a staged gradient construction process to sequentially form a high-entropy alloy bottom layer, a transition layer, and a high-entropy carbide surface strengthening layer. During the preparation stage of the transition layer, multiple parameters such as source voltage, workpiece bias voltage, carbon-containing gas flow rate, and the distance between the source and workpiece electrodes are simultaneously controlled to reduce the influence of spontaneous diffusion on the gradient layer. This facilitates the control of the gradient interval width and the enrichment degree of surface elements, and reduces the occurrence of problems such as surface component saturation and excessively rapid decay of internal element gradients.

[0024] 2. In this invention, the gradual increase of electrical parameters and the gradual reduction of electrode spacing work together to progressively enhance plasma bombardment energy and diffusion driving force, thereby achieving the control of gradient distribution. This allows the element diffusion depth to match the concentration distribution and energy input, thereby reducing the influence of spontaneous diffusion under fixed parameters and further improving the uniformity of composition and performance at each depth of the gradient layer. Attached Figure Description

[0025] The accompanying drawings, which are included to provide a further understanding of the invention and form part of this application, illustrate exemplary embodiments of the invention and, together with their description, serve to explain the invention and do not constitute an undue limitation thereof. In the drawings:

[0026] Figure 1 This is a flowchart of the preparation method in this invention. Detailed Implementation

[0027] The technical solutions of the embodiments of the present invention will be clearly and completely described below with reference to the accompanying drawings. Obviously, the described embodiments are only some embodiments of the present invention, and not all embodiments. Based on the embodiments of the present invention, all other embodiments obtained by those skilled in the art without creative effort are within the scope of protection of the present invention.

[0028] like Figure 1 As shown, this invention provides a method for preparing high-entropy carbide gradient solid solution reinforced layers using dual-glow plasma metallurgy.

[0029] Example 1

[0030] S1. The titanium alloy substrate is polished with sandpaper of grit 240-1200#, polishing from coarse to fine. The titanium alloy substrate is then ultrasonically cleaned and dried in acetone solution. The high-entropy alloy is polished with sandpaper of grit 240-2000#, polishing from coarse to fine. The high-entropy alloy is then ultrasonically cleaned and dried in anhydrous ethanol. The elements and their proportions in the high-entropy alloy target material are as follows: Ti: 8.09%, Zr: 15.42%, Hf: 30.18%, Nb: 15.71%, Ta: 30.60%.

[0031] S2. Place the pretreated titanium alloy substrate on the workpiece electrode of the dual-glow plasma device, place the high-entropy alloy target on the source electrode of the dual-glow plasma device, and lock the workpiece electrode and source electrode spacing adjustment mechanism. The spacing between the source electrode and the workpiece electrode is 18.5mm.

[0032] S3. Seal the double-glowing plasma equipment, evacuate the cavity, and then introduce argon gas with a purity of ≥99.99% into the inner cavity of the double-glowing plasma equipment. After stabilizing the cavity pressure to 40pa, turn on the workpiece bias power supply and the source voltage power supply. The workpiece bias voltage is -350V, the source voltage is 730V, and the processing time is 20min to remove the surface oxide film.

[0033] S4. Maintain stable chamber pressure, argon flow rate of 40 sccm, and simultaneously increase source voltage and workpiece bias voltage. Increase source voltage to 920V and workpiece bias voltage to -520V, perform low-rate sputtering, sputtering time of 40 min, and form a 2μm high-entropy alloy underlayer on the surface of titanium alloy substrate.

[0034] S5. Open the methane pipeline valve, adjust the source electrode voltage from 920V to 1130V at a constant rate, adjust the workpiece electrode bias voltage from -520V to -710V, increase the methane gas flow rate from 0sccm to 12sccm, gradually decrease the distance between the source electrode and the workpiece electrode from 18.5mm to 11mm, form the transition layer in 50min, and the thickness of the transition layer is 3.5μm.

[0035] S6. Stabilize the source voltage at 1130V, the workpiece bias voltage at -710V, the methane gas flow rate at 12sccm, and the electrode spacing at 11mm, and maintain the stabilization time for 70min to form a high-entropy carbide reinforcement layer with a thickness of 7.5μm on the substrate surface.

[0036] S7. Reduce the source voltage and workpiece bias voltage to zero, reduce the carbon-containing gas flow rate until the carbon-containing gas pipeline valve is closed, close the valve on the argon gas inlet pipeline, and cool the substrate with the furnace at a cooling rate of 8℃ / min. Remove the substrate after it has cooled to room temperature of 25℃.

[0037] Example 2

[0038] S1. The titanium alloy substrate is polished with sandpaper of grit 240-1200#, polishing from coarse to fine. The titanium alloy substrate is then ultrasonically cleaned and dried in acetone solution. The high-entropy alloy is polished with sandpaper of grit 240-2000#, polishing from coarse to fine. The high-entropy alloy is then ultrasonically cleaned and dried in anhydrous ethanol. The elements and their proportions in the high-entropy alloy target material are as follows: Ti: 8.09%, Zr: 15.42%, Hf: 30.18%, Nb: 15.71%, Ta: 30.60%.

[0039] S2. Place the pretreated titanium alloy substrate on the workpiece electrode of the dual-glow plasma device, place the high-entropy alloy target on the source electrode of the dual-glow plasma device, and lock the workpiece electrode and source electrode spacing adjustment mechanism. The spacing between the source electrode and the workpiece electrode is 18.5mm.

[0040] S3. Seal the double-glowing plasma equipment, evacuate the cavity, and then introduce argon gas with a purity of ≥99.99% into the inner cavity of the double-glowing plasma equipment. After stabilizing the cavity pressure to 40pa, turn on the workpiece extreme bias power supply and the source voltage power supply. The workpiece extreme bias voltage is -405V, the source voltage is 730V, and the processing time is 20min to remove the surface oxide film.

[0041] S4. Maintain stable chamber pressure, argon flow rate of 40 sccm, and simultaneously increase source voltage and workpiece bias voltage. Increase source voltage to 920V and workpiece bias voltage to -570V, perform low-rate sputtering for 40 minutes to form a 2.3μm high-entropy alloy underlayer on the surface of titanium alloy substrate.

[0042] S5. Open the methane pipeline valve, adjust the source electrode voltage from 920V to 1130V at a constant rate, adjust the workpiece electrode bias voltage from -570V to -795V, increase the methane gas flow rate from 0sccm to 12sccm, gradually decrease the distance between the source electrode and the workpiece electrode from 18.5mm to 11mm, form the transition layer in 50min, and the thickness of the transition layer is 4.3μm.

[0043] S6. Stabilize the source voltage at 1130V, the workpiece bias voltage at -795V, the methane gas flow rate at 12sccm, and the electrode spacing at 11mm, and maintain the stabilization time for 70min to form a high-entropy carbide reinforcement layer with a thickness of 7.2μm on the substrate surface.

[0044] S7. Reduce the source voltage and workpiece bias voltage to zero, reduce the carbon-containing gas flow rate until the carbon-containing gas pipeline valve is closed, close the valve on the argon gas inlet pipeline, and cool the substrate with the furnace at a cooling rate of 8℃ / min. Remove the substrate after it has cooled to room temperature of 25℃.

[0045] Example 3

[0046] S1. The titanium alloy substrate is polished with sandpaper of grit 240-1200#, polishing from coarse to fine. The titanium alloy substrate is then ultrasonically cleaned and dried in acetone solution. The high-entropy alloy is polished with sandpaper of grit 240-2000#, polishing from coarse to fine. The high-entropy alloy is then ultrasonically cleaned and dried in anhydrous ethanol. The elements and their proportions in the high-entropy alloy target material are as follows: Ti: 8.09%, Zr: 15.42%, Hf: 30.18%, Nb: 15.71%, Ta: 30.60%.

[0047] S2. Place the pretreated titanium alloy substrate on the workpiece electrode of the dual-glow plasma device, place the high-entropy alloy target on the source electrode of the dual-glow plasma device, and lock the workpiece electrode and source electrode spacing adjustment mechanism. The spacing between the source electrode and the workpiece electrode is 18.5mm.

[0048] S3. Seal the double-glowing plasma equipment, evacuate the cavity, and then introduce argon gas with a purity of ≥99.99% into the inner cavity of the double-glowing plasma equipment. After stabilizing the cavity pressure to 40pa, turn on the workpiece bias power supply and the source voltage power supply. The workpiece bias voltage is -473V, the source voltage is 730V, and the processing time is 20min to remove the surface oxide film.

[0049] S4. Maintain stable chamber pressure, argon flow rate of 40 sccm, and simultaneously increase source voltage and workpiece bias voltage. Increase source voltage to 920V and workpiece bias voltage to -665V, perform low-rate sputtering for 40 minutes to form a 2.3μm high-entropy alloy underlayer on the surface of titanium alloy substrate.

[0050] S5. Open the methane pipeline valve, adjust the source electrode voltage from 920V to 1130V at a constant rate, adjust the workpiece electrode bias voltage from -665V to -845V, increase the methane gas flow rate from 0sccm to 12sccm, gradually decrease the distance between the source electrode and the workpiece electrode from 18.5mm to 11mm, form the transition layer in 50min, and the thickness of the transition layer is 3.7μm.

[0051] S6. Stabilize the source voltage at 1130V, the workpiece bias voltage at -845V, the methane gas flow rate at 12sccm, and the electrode spacing at 11mm, and maintain the stabilization time for 70min to form a high-entropy carbide reinforcement layer with a thickness of 7.3μm on the surface of the substrate.

[0052] S7. Reduce the source voltage and workpiece bias voltage to zero, reduce the carbon-containing gas flow rate until the carbon-containing gas pipeline valve is closed, close the valve on the argon gas inlet pipeline, and cool the substrate with the furnace at a cooling rate of 8℃ / min. Remove the substrate after it has cooled to room temperature of 25℃.

[0053] Example 4

[0054] S1. The titanium alloy substrate is polished with sandpaper of grit 240-1200#, polishing from coarse to fine. The titanium alloy substrate is then ultrasonically cleaned and dried in acetone solution. The high-entropy alloy is polished with sandpaper of grit 240-2000#, polishing from coarse to fine. The high-entropy alloy is then ultrasonically cleaned and dried in anhydrous ethanol. The elements and their proportions in the high-entropy alloy target material are as follows: Ti: 8.09%, Zr: 15.42%, Hf: 30.18%, Nb: 15.71%, Ta: 30.60%.

[0055] S2. Place the pretreated titanium alloy substrate on the workpiece electrode of the dual-glow plasma device, place the high-entropy alloy target on the source electrode of the dual-glow plasma device, and lock the workpiece electrode and source electrode spacing adjustment mechanism. The spacing between the source electrode and the workpiece electrode is 18.5mm.

[0056] S3. Seal the Shuanghui plasma equipment, evacuate the cavity, and then introduce argon gas with a purity of ≥99.99% into the inner cavity of the Shuanghui plasma equipment. After stabilizing the cavity pressure to 40pa, turn on the workpiece bias power supply and the source voltage power supply. The workpiece bias voltage is -405V, the source voltage is 785V, and the processing time is 20min to remove the surface oxide film.

[0057] S4. Maintain stable chamber pressure, argon flow rate of 40 sccm, and simultaneously increase source voltage and workpiece bias voltage. Increase source voltage to 1013V and workpiece bias voltage to -570V, perform low-rate sputtering for 40 minutes to form a 2.4μm high-entropy alloy underlayer on the surface of titanium alloy substrate.

[0058] S5. Open the methane pipeline valve, adjust the source electrode voltage from 1013V to 1195V at a constant rate, adjust the workpiece electrode bias voltage from -570V to -795V, increase the methane gas flow rate from 0sccm to 12sccm, gradually decrease the distance between the source electrode and the workpiece electrode from 18.5mm to 11mm, form the transition layer in 50min, and the thickness of the transition layer is 4.5μm.

[0059] S6. Stabilize the source voltage at 1195V, the workpiece bias voltage at -795V, the methane gas flow rate at 12sccm, and the electrode spacing at 11mm, and maintain the stabilization time for 70min to form a high-entropy carbide reinforcement layer with a thickness of 7.7μm on the surface of the substrate.

[0060] S7. Reduce the source voltage and workpiece bias voltage to zero, reduce the carbon-containing gas flow rate until the carbon-containing gas pipeline valve is closed, close the valve on the argon gas inlet pipeline, and cool the substrate with the furnace at a cooling rate of 8℃ / min. Remove the substrate after it has cooled to room temperature of 25℃.

[0061] Example 5

[0062] S1. The titanium alloy substrate is polished with sandpaper of grit 240-1200#, polishing from coarse to fine. The titanium alloy substrate is then ultrasonically cleaned and dried in acetone solution. The high-entropy alloy is polished with sandpaper of grit 240-2000#, polishing from coarse to fine. The high-entropy alloy is then ultrasonically cleaned and dried in anhydrous ethanol. The elements and their proportions in the high-entropy alloy target material are as follows: Ti: 8.09%, Zr: 15.42%, Hf: 30.18%, Nb: 15.71%, Ta: 30.60%.

[0063] S2. Place the pretreated titanium alloy substrate on the workpiece electrode of the dual-glow plasma device, place the high-entropy alloy target on the source electrode of the dual-glow plasma device, and lock the workpiece electrode and source electrode spacing adjustment mechanism. The spacing between the source electrode and the workpiece electrode is 18.5mm.

[0064] S3. Seal the Shuanghui plasma equipment, evacuate the cavity, and then introduce argon gas with a purity of ≥99.99% into the inner cavity of the Shuanghui plasma equipment. After stabilizing the cavity pressure to 40pa, turn on the workpiece bias power supply and the source voltage power supply. The workpiece bias voltage is -405V, the source voltage is 867V, and the processing time is 20min to remove the surface oxide film.

[0065] S4. Maintain stable chamber pressure, argon flow rate of 40 sccm, and simultaneously increase source voltage and workpiece bias voltage. Increase source voltage to 1088V and workpiece bias voltage to -570V, perform low-rate sputtering for 40 minutes to form a 2.6μm high-entropy alloy underlayer on the surface of titanium alloy substrate.

[0066] S5. Open the methane pipeline valve, adjust the source electrode voltage from 1088V to 1274V at a constant rate, adjust the workpiece electrode bias voltage from -570V to -795V, increase the methane gas flow rate from 0sccm to 12sccm, gradually decrease the distance between the source electrode and the workpiece electrode from 18.5mm to 11mm, form the transition layer in 50min, and the thickness of the transition layer is 5.3μm.

[0067] S6. Stabilize the source voltage at 1274V, the workpiece bias voltage at -795V, the methane gas flow rate at 12sccm, and the electrode spacing at 11mm, and maintain the stabilization time for 70min to form a high-entropy carbide reinforcement layer with a thickness of 8.4μm on the substrate surface.

[0068] S7. Reduce the source voltage and workpiece bias voltage to zero, reduce the carbon-containing gas flow rate until the carbon-containing gas pipeline valve is closed, close the valve on the argon gas inlet pipeline, and cool the substrate with the furnace at a cooling rate of 8℃ / min. Remove the substrate after it has cooled to room temperature of 25℃.

[0069] Example 6

[0070] S1. The titanium alloy substrate is polished with sandpaper of grit 240-1200#, polishing from coarse to fine. The titanium alloy substrate is then ultrasonically cleaned and dried in acetone solution. The high-entropy alloy is polished with sandpaper of grit 240-2000#, polishing from coarse to fine. The high-entropy alloy is then ultrasonically cleaned and dried in anhydrous ethanol. The elements and their proportions in the high-entropy alloy target material are as follows: Ti: 8.09%, Zr: 15.42%, Hf: 30.18%, Nb: 15.71%, Ta: 30.60%.

[0071] S2. Place the pretreated titanium alloy substrate on the workpiece electrode of the dual-glow plasma device, place the high-entropy alloy target on the source electrode of the dual-glow plasma device, and lock the workpiece electrode and source electrode spacing adjustment mechanism. The spacing between the source electrode and the workpiece electrode is 17.3mm.

[0072] S3. Seal the Shuanghui plasma equipment, evacuate the cavity, and then introduce argon gas with a purity of ≥99.99% into the inner cavity of the Shuanghui plasma equipment. After stabilizing the cavity pressure to 40pa, turn on the workpiece bias power supply and the source voltage power supply. The workpiece bias voltage is -405V, the source voltage is 785V, and the processing time is 20min to remove the surface oxide film.

[0073] S4. Maintain stable chamber pressure, argon flow rate of 40 sccm, and simultaneously increase source voltage and workpiece bias voltage. Increase source voltage to 1013V and workpiece bias voltage to -570V, perform low-rate sputtering for 40 minutes to form a 2.6μm high-entropy alloy underlayer on the surface of titanium alloy substrate.

[0074] S5. Open the methane pipeline valve, adjust the source electrode voltage from 1013V to 1195V at a constant rate, adjust the workpiece electrode bias voltage from -570V to -795V, increase the methane gas flow rate from 0sccm to 12sccm, gradually decrease the distance between the source electrode and the workpiece electrode from 17.3mm to 11.4mm, form the transition layer in 50min, and the thickness of the transition layer is 4.7μm.

[0075] S6. Stabilize the source voltage at 1195V, the workpiece bias voltage at -795V, the methane gas flow rate at 12sccm, and the electrode spacing at 11.4mm, and maintain the stabilization time for 70min to form a high-entropy carbide reinforcement layer with a thickness of 7.6μm on the substrate surface.

[0076] S7. Reduce the source voltage and workpiece bias voltage to zero, reduce the carbon-containing gas flow rate until the carbon-containing gas pipeline valve is closed, close the valve on the argon gas inlet pipeline, and cool the substrate with the furnace at a cooling rate of 8℃ / min. Remove the substrate after it has cooled to room temperature of 25℃.

[0077] Example 7

[0078] S1. The titanium alloy substrate is polished with sandpaper of grit 240-1200#, polishing from coarse to fine. The titanium alloy substrate is then ultrasonically cleaned and dried in acetone solution. The high-entropy alloy is polished with sandpaper of grit 240-2000#, polishing from coarse to fine. The high-entropy alloy is then ultrasonically cleaned and dried in anhydrous ethanol. The elements and their proportions in the high-entropy alloy target material are as follows: Ti: 8.09%, Zr: 15.42%, Hf: 30.18%, Nb: 15.71%, Ta: 30.60%.

[0079] S2. Place the pretreated titanium alloy substrate on the workpiece electrode of the dual-glow plasma device, place the high-entropy alloy target on the source electrode of the dual-glow plasma device, and lock the workpiece electrode and source electrode spacing adjustment mechanism. The spacing between the source electrode and the workpiece electrode is 19.2 mm.

[0080] S3. Seal the Shuanghui plasma equipment, evacuate the cavity, and then introduce argon gas with a purity of ≥99.99% into the inner cavity of the Shuanghui plasma equipment. After stabilizing the cavity pressure to 40pa, turn on the workpiece bias power supply and the source voltage power supply. The workpiece bias voltage is -405V, the source voltage is 867V, and the processing time is 20min to remove the surface oxide film.

[0081] S4. Maintain stable chamber pressure, argon flow rate of 40 sccm, and simultaneously increase source voltage and workpiece bias voltage. Increase source voltage to 1088V and workpiece bias voltage to -570V, perform low-rate sputtering for 40 minutes to form a 2.2μm high-entropy alloy underlayer on the surface of titanium alloy substrate.

[0082] S5. Open the methane pipeline valve, adjust the source electrode voltage from 1088V to 1274V at a constant rate, adjust the workpiece electrode bias voltage from -570V to -795V, increase the methane gas flow rate from 0sccm to 12sccm, gradually decrease the distance between the source electrode and the workpiece electrode from 19.2mm to 10.5mm, form the transition layer in 50min, and the thickness of the transition layer is 4.1μm.

[0083] S6. Stabilize the source voltage at 1274V, the workpiece bias voltage at -795V, the methane gas flow rate at 12sccm, and the electrode spacing at 11mm, and maintain the stabilization time for 70min to form a high-entropy carbide reinforcement layer with a thickness of 7.5μm on the surface of the substrate.

[0084] S7. Reduce the source voltage and workpiece bias voltage to zero, reduce the carbon-containing gas flow rate until the carbon-containing gas pipeline valve is closed, close the valve on the argon gas inlet pipeline, and cool the substrate with the furnace at a cooling rate of 8℃ / min. Remove the substrate after it has cooled to room temperature of 25℃.

[0085] Example 8

[0086] S1. The titanium alloy substrate is polished with sandpaper of grit 240-1200#, polishing from coarse to fine. The titanium alloy substrate is then ultrasonically cleaned and dried in acetone solution. The high-entropy alloy is polished with sandpaper of grit 240-2000#, polishing from coarse to fine. The high-entropy alloy is then ultrasonically cleaned and dried in anhydrous ethanol. The elements and their proportions in the high-entropy alloy target material are as follows: Ti: 8.09%, Zr: 15.42%, Hf: 30.18%, Nb: 15.71%, Ta: 30.60%.

[0087] S2. Place the pretreated titanium alloy substrate on the workpiece electrode of the dual-glow plasma device, place the high-entropy alloy target on the source electrode of the dual-glow plasma device, and lock the workpiece electrode and source electrode spacing adjustment mechanism. The spacing between the source electrode and the workpiece electrode is 18.5mm.

[0088] S3. Seal the Shuanghui plasma equipment, evacuate the cavity, and then introduce argon gas with a purity of ≥99.99% into the inner cavity of the Shuanghui plasma equipment. After stabilizing the cavity pressure to 40pa, turn on the workpiece bias power supply and the source voltage power supply. The workpiece bias voltage is -405V, the source voltage is 785V, and the processing time is 20min to remove the surface oxide film.

[0089] S4. Maintain stable chamber pressure, argon flow rate of 40 sccm, and simultaneously increase source voltage and workpiece bias voltage. Increase source voltage to 1013V and workpiece bias voltage to -570V, perform low-rate sputtering for 40 minutes to form a 2.4μm high-entropy alloy underlayer on the surface of titanium alloy substrate.

[0090] S5. Open the methane pipeline valve, adjust the source electrode voltage from 1013V to 1195V at a constant rate, adjust the workpiece electrode bias voltage from -570V to -795V, increase the methane gas flow rate from 0sccm to 14sccm, gradually decrease the distance between the source electrode and the workpiece electrode from 18.5mm to 11mm, form the transition layer in 50min, and the thickness of the transition layer is 4.7μm.

[0091] S6. Stabilize the source voltage at 1195V, the workpiece bias voltage at -795V, the methane gas flow rate at 14sccm, and the electrode spacing at 11mm, and maintain the stabilization time for 70min to form a high-entropy carbide reinforcement layer with a thickness of 7.8μm on the substrate surface.

[0092] S7. Reduce the source voltage and workpiece bias voltage to zero, reduce the carbon-containing gas flow rate until the carbon-containing gas pipeline valve is closed, close the valve on the argon gas inlet pipeline, and cool the substrate with the furnace at a cooling rate of 8℃ / min. Remove the substrate after it has cooled to room temperature of 25℃.

[0093] Example 9

[0094] S1. The titanium alloy substrate is polished with sandpaper of grit 240-1200#, polishing from coarse to fine. The titanium alloy substrate is then ultrasonically cleaned and dried in acetone solution. The high-entropy alloy is polished with sandpaper of grit 240-2000#, polishing from coarse to fine. The high-entropy alloy is then ultrasonically cleaned and dried in anhydrous ethanol. The elements and their proportions in the high-entropy alloy target material are as follows: Ti: 8.09%, Zr: 15.42%, Hf: 30.18%, Nb: 15.71%, Ta: 30.60%.

[0095] S2. Place the pretreated titanium alloy substrate on the workpiece electrode of the dual-glow plasma device, place the high-entropy alloy target on the source electrode of the dual-glow plasma device, and lock the workpiece electrode and source electrode spacing adjustment mechanism. The spacing between the source electrode and the workpiece electrode is 18.5mm.

[0096] S3. Seal the Shuanghui plasma equipment, evacuate the cavity, and then introduce argon gas with a purity of ≥99.99% into the inner cavity of the Shuanghui plasma equipment. After stabilizing the cavity pressure to 40pa, turn on the workpiece bias power supply and the source voltage power supply. The workpiece bias voltage is -405V, the source voltage is 785V, and the processing time is 20min to remove the surface oxide film.

[0097] S4. Maintain stable chamber pressure, argon flow rate of 40 sccm, and simultaneously increase source voltage and workpiece bias voltage. Increase source voltage to 1013V and workpiece bias voltage to -570V, perform low-rate sputtering for 40 minutes to form a 2.4μm high-entropy alloy underlayer on the surface of titanium alloy substrate.

[0098] S5. Open the methane pipeline valve, adjust the source electrode voltage from 1013V to 1195V at a constant rate, adjust the workpiece electrode bias voltage from -570V to -795V, increase the methane gas flow rate from 0sccm to 18sccm, gradually decrease the distance between the source electrode and the workpiece electrode from 18.5mm to 11mm, form the transition layer in 50min, and the thickness of the transition layer is 4.3μm.

[0099] S6. Stabilize the source voltage at 1195V, the workpiece bias voltage at -795V, the methane gas flow rate at 18sccm, and the electrode spacing at 11mm, and maintain the stabilization time for 70min to form a high-entropy carbide reinforcement layer with a thickness of 7.4μm on the substrate surface.

[0100] S7. Reduce the source voltage and workpiece bias voltage to zero, reduce the carbon-containing gas flow rate until the carbon-containing gas pipeline valve is closed, close the valve on the argon gas inlet pipeline, and cool the substrate with the furnace at a cooling rate of 8℃ / min. Remove the substrate after it has cooled to room temperature of 25℃.

[0101] Alloys with gradient layers were prepared according to Examples 1-9. The properties of the gradient layers of the prepared alloys were tested using the following experimental methods, including testing their thickness, tribological properties, corrosion resistance, and high-temperature oxidation resistance.

[0102] Thickness measurement: The cross-sectional observation method of scanning electron microscopy was adopted. After the sample was cut, mounted, polished and slightly corroded, the cross-sectional morphology of the gradient layer was photographed by scanning electron microscopy. The thickness of the high-entropy alloy bottom layer, transition layer and high-entropy carbide solid solution reinforcement layer was measured layer by layer. Five observation positions were selected for each group of samples and the arithmetic mean was taken.

[0103] Friction and wear performance testing: The ball-and-disc friction and wear test method was adopted, and the following parameters were selected. Using ceramic balls as a friction pair, a room temperature friction test was conducted with a fixed load, rotational speed, friction radius, and test duration. The steady-state friction coefficient was recorded, and the wear rate of the sample was calculated by measuring the cross-sectional profile of the wear track using a profilometer. ).

[0104] Corrosion resistance testing: An electrochemical three-electrode test method was used, with a sample with a gradient layer as the working electrode, a saturated calomel electrode as the reference electrode, and a platinum sheet as the counter electrode. Potentiodynamic polarization testing was conducted in a 3.5 wt.% NaCl aqueous solution to measure the self-corrosion potential. ) and self-corrosion current density ( ), to evaluate the corrosion resistance of the sample.

[0105] High-temperature antioxidant performance testing: The isothermal thermogravimetric oxidation test method was adopted. The sample was placed in an air atmosphere and heated to a set temperature and oxidized at a constant temperature for a long time. The mass change of the sample was continuously recorded using a synchronous thermal analysis balance, and the weight gain per unit area was calculated. ), characterizing the high-temperature oxidation resistance level of the sample.

[0106] The data obtained from the above experiments are shown in Table (1):

[0107] Example thickness steady-state friction coefficient Wear rate Self-corrosion potential Corrosion current density Oxidative weight gain at 650℃ / 100h Example 1 13.0 0.462 5.71 -0.431 8.26 0.364 Example 2 13.8 0.435 4.83 -0.406 6.74 0.321 Example 3 13.3 0.451 5.26 -0.419 7.35 0.342 Example 4 14.6 0.407 3.84 -0.392 4.68 0.283 Example 5 16.3 0.416 4.12 -0.385 5.03 0.287 Example 6 14.9 0.41 3.95 -0.378 4.56 0.274 Example 7 13.8 0.443 5.07 -0.412 7.01 0.33 Example 8 14.9 0.414 4.03 -0.381 4.72 0.279 Example 9 14.1 0.431 4.68 -0.401 6.35 0.312

[0108] Table (1)

[0109] Compared with Examples 1-9, Example 4 has the lowest steady-state friction coefficient of 0.407, the lowest wear rate, a relatively positive self-corrosion potential, a low corrosion current density, and a small weight gain due to long-term oxidation at 650℃. The thickness ratio of the three layers is also balanced, making it the preferred embodiment of the present invention.

[0110] Comparative Example 1

[0111] S1. The titanium alloy substrate sample was polished step by step with 0# to 07# sandpaper, polished with 2.5μm diamond polishing paste, ultrasonically cleaned in acetone solution and dried.

[0112] S2. Use 01# sandpaper to polish the surface of the CoCrNiAlTi high-entropy alloy target and the NiCoCrAlY alloy target to remove the oxide layer. Then, ultrasonically clean and dry them in anhydrous ethanol before placing them in a dual-glow device. The CoCrNiAlTi target contains the following mass percentages of elements: Co 20%, Cr 22%, Ni 23%, Al 10%, Ti 25%; the NiCoCrAlY target contains the following mass percentages of elements: Ni 43%, Co 25%, Cr 23.3%, Al 8%, Y 0.7%.

[0113] S3. Place the titanium alloy substrate sample in the dual-light device, with the titanium alloy substrate as the workpiece electrode and the CoCrNiAlTi target as the source electrode. Set the distance between the source electrode and the workpiece electrode (the distance between the lower surface of the target and the upper surface of the sample) to 14 mm and close the chamber.

[0114] S4. Turn on the cooling circulating water and mechanical pump, evacuate to below 0.5Pa, introduce argon gas for gas washing, and when the chamber pressure reaches 200Pa, adjust the argon gas flow rate to 0, evacuate to below 0.5Pa, and repeat the above gas washing steps 4 times.

[0115] S5. Adjust the argon flow rate to 60 sccm, control the mechanical pump valve to stabilize the gas pressure in the furnace at 41 Pa, turn on the workpiece electrode power supply and increase the voltage to 300 V, use glow discharge to clean the sample surface for 10 min, turn on the CoCrNiAlTi source electrode power supply and increase the voltage to 300 V, and clean the target surface for 10 min.

[0116] S6. After the glow discharge stabilizes, the voltage is simultaneously increased. The source electrode voltage is slowly increased to 1000V and the workpiece electrode voltage is increased to 550V. The temperature is maintained for 1 hour to obtain a CoCrNiAlTi high-entropy alloy coating on the surface of the titanium alloy substrate 1.

[0117] S7. Switch to NiCoCrAlY source power supply, use the sample obtained in step S6 as the workpiece electrode, adjust the air pressure to 40Pa, slowly increase the source voltage to 920V, adjust the workpiece electrode voltage to 480V, keep warm for 3h, and obtain NiCoCrAlY adhesive layer on the surface of CoCrNiAlTi high entropy alloy coating 2.

[0118] S8. After 50 minutes, slowly reduce the source and workpiece voltages to 0, turn off the source and workpiece power supplies, turn off the argon flow, evacuate to below 0.5 Pa, turn off the mechanical pump, equipment power supply, and circulating water, and remove the sample after cooling for 4 hours.

[0119] In this comparative example, the gradient layer's performance was tested using the same experimental method as in Examples 1-9, and the results are as follows:

[0120] The gradient layer has a total thickness of 15.2 μm, a steady-state friction coefficient of 0.441, a wear rate of 4.76, a self-corrosion potential of -0.305, a corrosion current density of 4.03, and an oxidation weight gain of 0.265 at 650℃ / 100h. The alloy gradient layer in this comparative example has good corrosion resistance, and the oxidation weight gain is only slightly higher than that in Example 4. However, the steady-state friction coefficient and wear rate are significantly increased, and the wear resistance performance is significantly different. Therefore, compared with Example 4, Example 4 is a better manufacturing scheme.

[0121] Comparative Example 2

[0122] S1. Place the steel substrate, Cr target, and TiVCr target into the sputtering chamber of the magnetron sputtering equipment;

[0123] S2. Evacuate the sputtering cavity to a vacuum level lower than [missing information]. Pa, inert argon gas is introduced as a protective gas at a flow rate of 10 sccm and a purity of 99.9%, and the deposition pressure is adjusted to 0.8 Pa;

[0124] S3. Adjust the power supply pre-sputtering power to 100W, open the upper baffle of the Cr target, close the upper baffle of the TiVCr target, and pre-sputter for 15 minutes. Then close the upper baffle of the Cr target and open the upper baffle of the TiVCr target at the same time. Pre-sputter for 15 minutes. After the pre-sputtering is completed, adjust the upper baffles of the Cr target and the TiVCr target so that they are both in the closed state.

[0125] S4. Keep the baffle at the top of the TiVCr target closed, open the baffle at the top of the Cr target, set the substrate rotation speed to 10 r / min, substrate bias voltage to -80V, deposition power to 80W, and keep the substrate temperature at 200℃ throughout the deposition process. Deposit for 60 min to deposit a Cr diffusion layer on the steel substrate surface.

[0126] S5. Close the baffle at the top of the Cr target and open the baffle at the top of the TiVCr target. The substrate rotation speed is 10r / min, the substrate bias voltage is -120V, the deposition power is 120W, and the substrate temperature is kept constant at 200℃ throughout the deposition process. Deposition takes 60min. After natural cooling, the equipment is turned off and the sample is taken out. A TiVCr intermediate entropy alloy intermediate layer is deposited on the surface of the Cr diffusion layer.

[0127] S6. Place the product obtained in step S5 and the TiVCrZrNb target material into a double-layer glow plasma surface metallurgy equipment, using the sample as the workpiece electrode and the TiVCrZrNb alloy target material as the source electrode, and adjust the electrode spacing to 10mm.

[0128] S7. Turn on the circulating cooling water to evacuate the chamber to below 0.1 Pa, purge with argon gas twice, and then maintain the pressure at 30 Pa.

[0129] S8. Turn on the source power supply and the workpiece power supply, keep the glow discharge stable, slowly increase the source voltage to 400V, and perform double-layer glow discharge plasma cleaning on the surface of TiVCrZrNb alloy target for 30 minutes.

[0130] S9. While maintaining the glow discharge in the furnace, slowly increase the source voltage to 800V and the workpiece voltage to 400V at the same time. Then, keep the temperature for 3 hours to prepare a TiVCrZrNb high-entropy alloy diffusion layer and a TiVCrZrNb high-entropy alloy deposition layer on the sample surface.

[0131] S10. After the holding time is reached, slowly reduce the source and workpiece voltages to 0, pump the gas pressure to below 0.1 Pa, turn off the power, and after cooling for 7 hours, take out the sample.

[0132] In this comparative example, the gradient layer's performance was tested using the same experimental method as in Examples 1-9, and the results are as follows:

[0133] The gradient layer has a total thickness of 14.7 μm, a steady-state friction coefficient of 0.407, a wear rate of 3.62, a self-corrosion potential of -0.384, a corrosion current density of 4.97, and an oxidation weight gain of 0.316 at 650℃ / 100h. The alloy gradient layer in this comparative example has good wear resistance. However, its high-temperature oxidation resistance and corrosion resistance are weaker than those of Example 4, and its overall protective performance is also weaker than that of Example 4. Therefore, compared with Example 4, Example 4 is a better manufacturing scheme.

[0134] Comparative Example 3

[0135] S1. Select pure metal elements of Fe, Co, Cr, Al, Ti, and Cu with a purity ≥ 99.95%, weigh them according to the component ratio of FeCoCrAl0.5TiCu0.5, prepare 40 parts of raw materials, each part being 20g, and then clean and dry the raw materials with ultrasonic cleaning for later use.

[0136] S2. Clean the furnace cavity of the vacuum arc melting furnace, place the pretreated raw materials inside, turn on the power supply and cooling circulation system, evacuate to below 20Pa, and then purge with high-purity argon gas. Repeat this process at least three times, then evacuate again to... Pa, purged with argon to 0.08 Pa, magnetic stirring function was turned on, each part of raw material was turned over and melted repeatedly more than 3 times, heated and melted by edge and center, and cast into shape. The mold specifications were 8 mm in diameter and 10 mm in length. The sample was taken out of the furnace after cooling for 1 hour. The equipment was cleaned and the power and water were turned off to obtain rod-shaped high-entropy alloy source target.

[0137] S3. Clean the impurities inside the double glow plasma equipment furnace, close the furnace door, evacuate to below 1800Pa, turn on the source pulse power supply and gradually increase the voltage, bombard the target and substrate through glow discharge and arcing until the arcing phenomenon disappears, and the pretreatment is completed.

[0138] S4. Introduce argon, ammonia, and methane with a purity ≥99.99% into the furnace. The argon flow rate is 25 mL / min, and the ammonia and methane flow rates are both 3 mL / min. Adjust the gas pressure to 40 Pa, gradually increase the voltage and current of the pulse power supply, control the substrate temperature to 1200℃, and maintain the heat for 4.5 hours. After the heat maintenance is completed, turn off all process gases.

[0139] S5. Keep the equipment running, introduce ammonia gas with a purity of ≥99.99% at a flow rate of 120mL / min, adjust the ammonia gas flow rate to control the glow thickness to 7mm, adjust the pulse power supply negative bias voltage to -700V, control the nitriding temperature to 520℃, nitrid at a constant temperature for 8 hours, and then disconnect the power after nitriding. Let the workpiece cool to room temperature with the furnace.

[0140] S6. The plasma-modified substrate was ultrasonically cleaned with anhydrous ethanol for 20 min, blown dry, and then dried at 50℃ for 2 h for later use. Pure metal elements of Fe, Co, Cr, Al, Ti, and Cu with a purity ≥99.95% were selected, cleaned and dried, then arc-melted and vibrated to crush them. According to the target composition ratio, they were ball-milled at a speed of 40 r / min and a ball-to-material ratio of 16:1 for 5 h to obtain 250 mesh uniform high-entropy alloy powder.

[0141] S7. Mix 95% by mass of high-entropy alloy powder with 5% by mass of anhydrous ethanol until viscous, coat evenly on the substrate surface, dry at 60℃ for 5h, and then perform laser cladding on the pre-coated layer under argon protection at 25L / min using a laser power of 3500W, a scanning speed of 5mm / s, and a spot diameter of 3mm.

[0142] S8. Pure metal elements are melted by electric arc and crushed by vibration. Then, they are ball-milled for 1.5 hours at a speed of 260 r / min, a ball-to-material ratio of 11:1 and a reversing frequency of 40 Hz to obtain alloy powder with an average particle size of 80 μm. Sputtering target material is prepared by pressure sintering at 240 MPa and 1000℃ for 10 minutes under argon protection. At the same time, the laser cladding sample is ultrasonically cleaned with anhydrous ethanol for 20 minutes, blown dry and dried at 50℃ for 2 hours for later use.

[0143] S9. Install the high-entropy alloy sintered target material onto the cathode of the magnetron sputtering equipment, fix the pretreated sample onto the anode, and evacuate to... Argon ion glow discharge cleaning was performed for 15 min under 5 Pa pressure and 700 V negative bias. Then, argon flow rate of 60 sccm, substrate temperature of 200℃, target-substrate distance of 8 cm, sputtering power of 100 W was maintained for continuous sputtering deposition for 50 min to complete the preparation of high entropy alloy composite coating.

[0144] In this comparative example, the gradient layer's performance was tested using the same experimental method as in Examples 1-9, and the results are as follows:

[0145] The gradient layer has a total thickness of 15.1 μm, a steady-state friction coefficient of 0.403, a wear rate of 3.83, a self-corrosion potential of -0.407, a corrosion current density of 5.65, and an oxidation weight gain of 0.338 at 650℃ / 100h. The alloy gradient layer in this comparative example has a relatively excellent steady-state friction coefficient and certain wear resistance advantages. However, its corrosion resistance and high-temperature oxidation resistance are weaker than those of Example 4. Therefore, Example 4 is a better manufacturing scheme in comparison.

[0146] The above are merely preferred embodiments of the present invention and are not intended to limit the present invention in any way. Those skilled in the art can readily implement the invention based on the accompanying drawings and the description above. However, any modifications, alterations, or variations made by those skilled in the art without departing from the scope of the present invention, using the disclosed technical content, are equivalent embodiments of the present invention. Furthermore, any modifications, alterations, or variations made to the above embodiments based on the essential technology of the present invention are still within the protection scope of the present invention.

Claims

1. A method for preparing a high-entropy carbide gradient solid solution reinforced layer using dual-glow plasma metallurgy, characterized in that, This method Includes the following steps, S1. Material pretreatment: The titanium alloy substrate and the high-entropy alloy target are polished, and the polished titanium alloy substrate and the high-entropy alloy target are placed in a solution for ultrasonic cleaning and drying. S2. Material installation: Place the pretreated titanium alloy substrate on the workpiece electrode of the dual-glow plasma device, place the high-entropy alloy target on the source electrode of the dual-glow device, and lock the workpiece electrode and source electrode spacing adjustment mechanism. S3. Oxide film treatment: Seal the double glow plasma equipment, evacuate the cavity, introduce inert gas into the inner cavity of the double glow plasma equipment, stabilize the cavity gas pressure, turn on the workpiece extreme bias power supply and the source voltage power supply to remove the surface oxide film. S4. Forming the bottom layer: Maintaining stable inert gas flow and cavity pressure, simultaneously increasing source voltage and workpiece bias voltage, performing low-rate sputtering to form a high-entropy alloy bottom layer on the surface of the titanium alloy substrate. S5. Forming a transition layer: Open the valve of the carbon-containing gas pipeline, adjust the source electrode voltage, workpiece electrode bias voltage and carbon-containing gas flow rate synchronously at a constant rate, and gradually reduce the distance between the source electrode and the workpiece electrode through the adjustment mechanism to form a transition layer. S6. Forming a surface layer: The source voltage, workpiece bias voltage, carbon-containing gas flow rate and electrode spacing are set stably and maintained for a stable time to form a high-entropy carbide reinforcement layer on the surface of the substrate. S7. Cooling and Removing the Part: Reduce the source voltage and workpiece bias voltage to zero, reduce the flow rate of carbon-containing gas until the valve on the carbon-containing gas pipeline is closed, close the valve on the inert gas inlet pipeline, and remove the substrate after it has cooled to room temperature with the furnace.

2. The method for preparing a high-entropy carbide gradient solid solution reinforced layer by double-glow plasma metallurgy according to claim 1, characterized in that: In S1, the titanium alloy substrate is polished with sandpaper of grit 240 to 1200#, polishing from coarse to fine. The titanium alloy substrate is then cleaned in an acetone solution.

3. The method for preparing a high-entropy carbide gradient solid solution reinforced layer by double-glow plasma metallurgy according to claim 2, characterized in that: In S1, the high-entropy alloy is polished with sandpaper of grits ranging from 240 to 2000#, polishing from coarse to fine. The high-entropy alloy is then cleaned in anhydrous ethanol. The elements and their proportions in the high-entropy alloy target material are as follows: Ti: 8.09%, Zr: 15.42%, Hf: 30.18%, Nb: 15.71%, Ta: 30.60%.

4. The method for preparing a high-entropy carbide gradient solid solution reinforced layer by double-glow plasma metallurgy according to claim 1, characterized in that: In S3, the inert gas is argon with a purity of ≥99.99%, the cavity pressure is stable at 30-50 Pa, the workpiece bias voltage is -300 to -500 V, the source voltage is 700-900 V, and the processing time is 10-30 min.

5. The method for preparing a high-entropy carbide gradient solid solution reinforced layer by double-glow plasma metallurgy according to claim 1, characterized in that: In S4, the argon flow rate is 30–50 sccm, the source voltage is increased to 900–1100 V, the workpiece bias voltage is increased to -500–-700 V, and the sputtering time is 30–60 min.

6. The method for preparing a high-entropy carbide gradient solid solution reinforced layer by double-glow plasma metallurgy according to claim 1, characterized in that: In S5, the carbon-containing gas is methane. The source voltage is adjusted from 900-1100V to 1100-1300V, the workpiece bias voltage is adjusted from -500--700V to -700--900V, the carbon-containing gas flow rate is increased from 0 sccm to 10-20 sccm, the distance between the source and workpiece electrodes is gradually reduced from 15-20 mm to 10-12 mm, and the time to form the transition layer is 30-90 min.

7. The method for preparing a high-entropy carbide gradient solid solution reinforced layer by double-glow plasma metallurgy according to claim 1, characterized in that: In S6, the source voltage is 1100~1300V, the workpiece bias voltage is -700~-900V, the carbon-containing gas flow rate is 10~20sccm, the electrode spacing is 10~12mm, and the stabilization time is 60~120min.

8. The method for preparing a high-entropy carbide gradient solid solution reinforced layer by double-glow plasma metallurgy according to claim 1, characterized in that: In S7, the cooling rate is 5-10℃ / min, and the substrate is cooled to room temperature at 20-30℃.